Microencapsulation of Furacilin as a Method of Creating New Medicinal Forms, Possessing with Increased Biological Accessibility and Prolongable Effect - Kudryavtseva, Tatyana N. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Furacilin (nitrofural) is an antibiotic widely used in the form of ointment for the initial treatment of wounds on both skin and mucous membranes. The present study was aimed to develop and formulate create long-acting furacilin-based formulations. Materials and Methods: Double coat microcapsules were prepared using â€œEudragitÂ®â€ as a water-insoluble biocompatible polymer(inner coat) and sodium alginate, guar gum, polyvinyl alcohol, or polyvinylpyrrolidone as water-soluble polymer (second coat). Quantitative analysis of the microcapsules was confirmed using a ultraviolet (UV)-1800 UV spectrometer (Shimadzu). Results and Discussion: The microcapsules were prepared by solvent extraction method microcapsules and double coated using water insoluble and soluble polymers. Prepared microcapsules were evaluated for morphological characteristics; particle size, distribution, and release kinetics of microcapsules were studied. Furacilin microcapsule images obtained using a Quanta 650 FEG microscope with an autoemission cathode. In vitro release kinetics show prolonged drug release of furacilin from microcapsules. Conclusion: Furacilin microcapsules seemed to be appropriate for prolonged release and easily applied to a bandage intended, for purulent wound treatment.